Copper and Bacteria Evolution, Homeostasis and Toxicity - Solioz, Marc (SpringerBriefs in Biometals,, 2018)
In the past two decades, great progress has been made in the understanding of copper as a bioelement. The book summarizes the current knowledge of copper toxicity, homeostasis and resistance in bacteria, in which proteins like copper ATPases, copper chaperones and copper-responsive regulators of gene expression play major roles. The author also discusses the metallation of cuproenzymes. The evolution of the use of copper by cells and of copper-homeostatic proteins are is also considered in this Brief.